2011
DOI: 10.1080/01635581.2011.609306
|View full text |Cite
|
Sign up to set email alerts
|

Milk Stimulates Growth of Prostate Cancer Cells in Culture

Abstract: Concern has been expressed about the fact that cows' milk contains estrogens and could stimulate the growth of hormone-sensitive tumors. In this study, organic cows' milk and two commercial substitutes were digested in vitro and tested for their effects on the growth of cultures of prostate and breast cancer cells. Cows' milk stimulated the growth of LNCaP prostate cancer cells in each of 14 separate experiments, producing an average increase in growth rate of over 30%. In contrast, almond milk suppressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Recent studies revealed that milk protein plays a key role in the development and modulation of prostate cancer cell proliferation [16,17,23]. Tate et al [16] reported that cow's milk stimulated the growth of prostate cancer cells (LNCaP) almost as much as digested whole milk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies revealed that milk protein plays a key role in the development and modulation of prostate cancer cell proliferation [16,17,23]. Tate et al [16] reported that cow's milk stimulated the growth of prostate cancer cells (LNCaP) almost as much as digested whole milk.…”
Section: Discussionmentioning
confidence: 99%
“…Tate et al [16] reported that cow's milk stimulated the growth of prostate cancer cells (LNCaP) almost as much as digested whole milk. Like our results, neither casein nor digested milk increased the growth of breast cancer cells (MCF-7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors such as exposure to ionizing radiation, inheriting certain genes such as BRCA1 and BRCA2, and, most importantly, lifestyle have been associated with an increase in the risk of breast cancer. For instance, the link between breast carcinogenesis and naturally occurring substances such as heterocyclic amines (HCAs), insulin-like growth hormone (IGF-I), animal estrogen (E2), and bovine leukaemia virus (BLV), which are ubiquitous in western and modern diets, have been substantiated with a vast body of evidence [4][5][6][7][8][9][10][11]. Nonetheless, not much has been done in updating the dietary guidelines and food policies to address the role of these substances, and similar ones, in cancer epidemic.…”
Section: Introductionmentioning
confidence: 99%